Surface charge accumulation and suppression on fullerene-filled epoxy-resin insulator under DC voltage - Zhang, Boya; Gao, Wenqiang; Hou, Yicen; Zhang, Guixin (IEEE transactions on dielectrics and electrical insulation, 2018)
Surface charge accumulation on the insulator surface and the resulting flashover voltage reduction are considered the primary factors to hinder the large-scale use of HVDC system, especially the gas-insulated system. In this study, Buckminster-fullerene C60 of different loadings is introduced into epoxy resin for the purpose of restricting the mobility of charge carriers within the material and thus suppressing the charge accumulation on the insulator surface under dc voltage. Experimental results have shown that with the addition of tiny amount of fullerene C60 into epoxy, the conductivity of the composites decreases significantly with the loading and reaches its minimum around 100∼200 ppm, which can be as low as 20% that of neat epoxy. By using the Kelvin-probe method and an advanced inversion algorithm, the surface charge distribution on the fullerene-filled epoxy resin insulators with different filler loadings are obtained. It is observed that the addition of 200 ppm fullerene C60 into epoxy resin can effectively suppress the charge accumulation on the insulator surface. The interfacial polarization model is adopted to interpret the mechanism of surface charge accumulation, which shows that reducing the bulk conductivity of the insulator can effectively suppress the surface charging. This paper provides a potential solution for engineering epoxy based insulators used for the dc power system.